Clawback law in the context of succession - Holliday, Jayne (London [England] : Hart Publishing, 2020)
"This book offers a global solution for determining the law applicable to a claim to clawback an inter vivos gift from a third party within the context of a succession. The book aims to identify an appropriate and applicable legal framework which supports legal certainty for cross-border estate planning and protects the legitimate expectations of the relevant parties. This is an area of private international law that has yet to be handled satisfactorily ? as can be seen by the inadequate treatment of clawback from third parties in the 1989 Hague Convention on the Law Applicable to Succession to the Estates of Deceased Persons, and the 2012 EU Succession Regulation."--
P. Luxembourg -- Q. Malta -- R. Netherlands -- S. Poland -- T. Portugal -- U. Romania -- V. Slovakia -- W. Slovenia -- X. Spain -- Y. Sweden -- Bibliography -- Index
Based on author's thesis (doctoral - University of Aberdeen, 2018).
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Conflict of laws -- Inheritance and succession; Conflict of laws -- Gifts; Revocation; Private international law & conflict of laws; Electronic books